Leakages from Macroprudential Regulations : The Case of Household-Specific Tools and Corporate Credit. (IMF Working Papers; Working Paper ;, 2021)
Sector-specific macroprudential regulations increase the riskiness of credit to other sectors. Using firm-level data, this paper computed the measures of the riskiness of corporate credit allocation for 29 advanced and emerging economies. Consistently across these measures, the paper finds that during credit expansions, an unexpected tightening of household-specific macroprudential tools is followed by a rise in riskier corporate lending. Quantitatively, such unexpected tightening during a period of rapid credit growth increases the riskiness of corporate credit by around 10 percent of the historical standard deviation. This result supports early policy interventions when credit vulnerabilities are still low, since sectoral leakages will be less important at this stage. Further evidence from bank lending standards surveys suggests that the leakage effects are stronger for larger firms compared to SMEs, consistent with recent evidence on the use of personal real estate as loan collateral by small firms.